Examining the preparation and ongoing support of adults to take their medications as prescribed in kidney transplantation. Issue 2 (16th October 2014) - Williams, Allison; Crawford, Kimberley; Manias, Elizabeth; Ellis, Christine; Mullins, Kim; Howe, Kathy; Kennedy, Elaine; Maney, Orla; Mark, Tia; Gregory, Debbie; Van Hardeveld, Emma; Yip, Doris; et al.
Abstract: Rationale, aims and objectives: The shortage of kidney donors and benefits of kidney transplantation make graft success imperative. Medication adherence is critical to prevent the risk of graft rejection. This paper examines how adults are prepared and supported by renal transplant co‐ordinators and pharmacists to take their medications as prescribed in kidney transplantation. Methods: Renal transplant co‐ordinators and pharmacists of all five hospitals offering adult kidney transplantation in Victoria, Australia, were interviewed between November 2013 and February 2014. All data underwent qualitative descriptive analysis. Results: Nine renal transplant co‐ordinators and six pharmacists were interviewed. Although there was no standardized approach to education or other evidence‐based strategies to facilitate medication adherence, there were similarities between sites. These similarities included printed information, pre‐transplant education sessions, the use of medication lists and medication administration aids, intensive education in hospital and ensuring an adequate supply of medications post‐discharge. Conclusions: Renal transplant co‐ordinators and pharmacists recognized the importance of early patient education concerning immunosuppressant medication. However, each site had developed their own way of preparing a patient for kidney transplantation and follow‐up in the acute hospital setting based on experience and practice. Other non‐educational strategies involving behavioural and emotional aspects were less common. Differences in usual care reinforce the necessity for evidence‐based health care for best patient outcomes.